Age dependency of primary tumor sites and metastases in patients with Ewing sarcoma. Issue 9 (1st June 2018) - Worch, Jennifer; Ranft, Andreas; DuBois, Steven G.; Paulussen, Michael; Juergens, Heribert; Dirksen, Uta
Abstract: Background: The median age of patients with Ewing sarcoma (EwS) at diagnosis is around 14–15 years. Older age is associated with a worse outcome. The correlation of age at diagnosis on sites of disease has not been fully described. Objective: The goal of this study was to evaluate the differences in sites of primary tumor and metastatic tumor involvement according to age groups. Design/method: EwS data from the Gesellschaft für Pädiatrische Onkologie und Hämatology (GPOH) database of the Cooperative Ewing Sarcoma Study (CESS) 81/86 and the European Intergroup Cooperative Ewing's Sarcoma Study EICESS 92 and the EUROpean Ewing tumor Working Initiative of National Groups ‐ 99‐Protocol (EURO‐E.W.I.N.G.‐99) study were analyzed. Patient and tumor characteristics were evaluated statistically using chi square tests. Results: The study population included 2, 635 patients with bone EwS. Sites of primary and metastatic tumors differed according to the age groups of young children (0–9 years), early adolescence (10–14 years), late adolescence (15–19 years), young adults (20–24 years), and adults (more than 24 years). Young children demonstrated the most striking differences in site of disease with a lower proportion of pelvic primary and axial tumors. They presented less often with metastatic disease at diagnosis. Conclusions: Site of primary and metastatic tumor involvement in EwS differs according to patient age. The biological and developmental etiology for these differences requires further investigations.